Stenen lezen bij de kolenzeef. Oranje Nassau I. Kopie van exemplaar in collectie van het Soc. Hist. Centrum, Maastricht
Stenen lezen bij de kolenzeef. Oranje Nassau I. Kopie van exemplaar in collectie van het Soc. Hist. Centrum, Maastricht.